Green marketing and purchase intention of Peruvian consumers. An empirical study. - Gerónimo-Varillas, Samuel César; Cano-Bustamante, Lidia Teresa; Panez-Bendezú, Miguel Humberto; Vargas-Merino, Jorge Alberto (LACCEI, 2024)
The purpose of this research is to determine the influence of green marketing on the purchase intention of Peruvians. This study had a quantitative approach, non-experimental design, cross-sectional and causal or explanatory correlational level. We worked with an infinite population, because the number of people residing in the study varies constantly. The technique used was the survey that was used in a sample of 159 people of both sexes, the instrument used was the questionnaire with 38 questions. In general, it was determined that there is a significant influence of the independent variable green marketing on the dependent variable purchase intention with a sig ANOVA = 0.000, and an R2=0.176, which indicates that the regression model has the virtuality to explain the purchase intention in 17.6%, product of green marketing, accepting the research hypothesis.